Possible Association of Periodontal Diseases With Helicobacter pylori Gastric Infection: A Systematic Review and Meta-Analysis - López-Valverde, Nansi; Macedo de Sousa, Bruno; López-Valverde, Antonio; Suárez, Ana; Rodríguez, Cinthia; Aragoneses, Juan Manuel (Frontiers in Medicine, 2022)
Some research has suggested that dental plaque and saliva could be reservoirs of Helicobacter pylori (H. pylori) and be capable of infecting or re-infecting the gastric mucosa after eradication, with certain studies showing a significant association between PD and gastric infection by this bacterium. An electronic search was performed in PubMed, EMBASE, and Web of Science databases with the terms “Helicobacter pylori AND periodontal diseases”; “Helicobacter pylori AND gingivitis”; “Helicobacter pylori AND chronic periodontitis”; “Helicobacter pylori AND periodontitis”; “Helicobacter pylori AND dental plaque”, to identify articles up to September 2021. The Newcastle-Ottawa scale was used to assess study quality. A meta-analysis was performed using RevMan 2020 (Cochane Collaboration) software. A total of 1,315 studies were identified and 12 were included, analyzing 226,086 patients with mean age between 10.5 and 63.4 years. The prevalence of H. pylori in the oral cavity ranged from 5.4 to 83.3%. A random-effects model was used to analyze the presence of H. pylori and subgroups were made according to the method of evaluation (PCR or RUT). Statistical significance was found in the overall analysis (p = 0.01). There is no clear evidence that H. pylori present in oral bacterial plaque causes gastric infection and vice versa. Systematic Review Registration www.INPLASY.COM, identifier: INPLASY2021100097.